Benedikt Hensel (ed.), Transjordan and the Southern Levant. New Approaches Regarding the Iron Age and the Persian Period from Hebrew Bible Studies and Archaeology. - Gienini , Olga (Antiguo Oriente, 2025)
The book focuses on Transjordanian regions from the early Iron Age I, down to the Hellenistic periods describing its integration within the Southern Levant and their connections with the areas of the Mediterranean, Egypt, and Mesopotamia along with their major political powers during these periods. It does so from a multidisciplinary perspective that includes archaeology, Hebrew Bible studies, social/cultural history, Assyriology, ancient history, and religious history.